Tuhfat al ahwadhi bi sharh jami' al_Tirmidhi - Muhammad Abdurrahman Ibn Abdurrahim al Mabari Kafuriy (Maktabah al Salafiyyah, 1964)
ws.jl.3-7.c.1/stoc6, jl.1,2=c.1; jl.3,4,5=c.1-2; jl.6,7,8=c.1; jl.1-2=c.1; jl.5-6=c.1; jl.7-8=c.1; jl.9-10=c.1